An investigation to ascertain whether or not time pressure influences the accuracy of final year student radiographers in abnormality detection when interpreting conventional appendicular trauma radiographs: A pilot study. Issue 3 (August 2020) - Whitaker, S.; Cox, W.A.S.
Abstract: Introduction: There is an increasing demand on diagnostic imaging departments, a shortage of radiologists, and a backlog of images requiring a report across several trusts in the UK. A negative impact on performance can result in significant outcomes for the patient. The aim of this study is to ascertain whether decisions made under time pressure will affect the accuracy of the interpretation of conventional radiographs. Methods: Final year undergraduate diagnostic radiography students were recruited [n = 21] and separated into three groups of seven at random, assigning time limits per image for a set of normal and abnormal conventional appendicular radiographs; 15 s (high pressure), 30 s (moderate pressure) and unlimited time (low pressure). Each image was assessed, and answers were recorded as normal or abnormal with an approximate location of the pathology. Results: The ANOVA test revealed no statistical significance amongst results. The mean accuracy was highest in the 15 s group (82.86%) and lowest in the unlimited time group (74.52%). The results also demonstrated a decrease in accuracy with increased image review times within the unlimited time group; with the quickest participant achieving 88.33% and the slowest, 56.67%. Conclusion: The results demonstrated no statistical significance. However, it is recommended to conduct a similar study using sufficient reporting practitioners to enable direct parallels to be drawn with statistical significance. Implications for practice: The results signify an importance for imaging departments to manage the number of staff and their workload. Subsequently, this aims to ensure reporting practitioners work at their optimum stress level for efficient work performance.